Method for producing highly water-absorbent resin

JP2025023144AInactive Publication Date: 2025-02-14LG CHEM LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024209025
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-17
Filing Date
2024-11-29
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

【0010】 本発明の高吸水性樹脂の製造方法によれば、優れた吸収性能を示し、同時に速い吸収速度および優れたゲル強度を同時に改善させた高吸水性樹脂を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025023144000001
    Figure 2025023144000001
  • Figure 2025023144000002
    Figure 2025023144000002
  • Figure 2025023144000003
    Figure 2025023144000003
Patent Text Reader

Abstract

To provide a highly water-absorbent resin composition and a producing method thereof, more concretely, a highly water-absorbent resin improved simultaneously in rapid absorption speed and excellent gel strength, by using specific additives in combination in a polymerization step, and a producing method thereof.SOLUTION: A method for producing a highly water-absorbent resin, comprising the steps of forming a hydrogel polymer containing a crosslinked polymer obtained by crosslinking a water-soluble ethylene-based unsaturated monomer having at least some neutralized acidic groups in the presence of an epoxy-based internal crosslinking agent, a chelating agent, and a capsule-type foaming agent; drying the hydrogel polymer to form a base resin powder; and thermally treating the base resin powder in the presence of a surface crosslinking agent to crosslink the surface of the base resin powder, wherein the epoxy-based internal crosslinking agent is ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, poly(ethylene glycol)n diglycidyl ether (n=4 to 13), or a combination thereof, and the capsule-type foaming agent has a structure comprising a core containing a hydrocarbon and a shell formed of a thermoplastic resin surrounding the core.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [Cross-reference to related applications] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0006720 filed on January 18, 2021, and Korean Patent Application No. 10-2022-0006530 filed on January 17, 2022, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a highly water-absorbent resin which has a fast absorption rate and excellent gel strength at the same time, and a method for producing the same, by using a combination of specific additives in the polymerization stage. [Background technology]

[0003] Super absorbent polymer (SAP) is a synthetic polymeric material that can absorb 500 to 1,000 times its own weight in water, and is given different names by different developers, such as SAM (Super Absorbency Material), AGM (Absorbent Gel Material), etc. Such super absorbent polymers were first put to practical use as sanitary products, and are now widely used in sanitary products such as baby diapers, as soil water retaining agents for gardening, water stoppers for civil engineering and construction, seedling sheets, freshness preserving agents in the food distribution field, and materials for poultices.

[0004] In most cases, such superabsorbent polymers are widely used in the field of sanitary materials, such as diapers and sanitary napkins. For these applications, they need to exhibit high absorbency for moisture and other substances, as well as excellent absorbency under pressure, so that absorbed moisture does not escape even when subjected to external pressure.

[0005] In addition, when the superabsorbent polymer is contained in a sanitary product such as a diaper, it is necessary to diffuse urine and the like as widely as possible even in an environment where it is pressurized by the weight of the user. This makes it possible to improve the absorption performance and absorption speed of the sanitary product by fully utilizing the superabsorbent polymer particles contained in the entire area of ​​the sanitary product's absorbent layer. In addition, due to such diffusion characteristics under pressure, it is possible to further improve the rewet characteristics of the diaper, which prevents urine and the like once absorbed by the superabsorbent polymer from leaking out again, and also to improve the leakage prevention characteristics of the diaper. Therefore, attempts have been made to improve the characteristics of diffusing urine and the like widely by changing the design of the sanitary product such as a diaper. However, in recent years, sanitary products have become thinner and the content of the superabsorbent polymer in the sanitary product has relatively increased, so that the improvement of the diffusion characteristics by changing the design of the sanitary product itself has reached its limit.

[0006] When superabsorbent polymers are included in sanitary products such as diapers, they come into direct contact with the skin of the user, so if urine, etc., absorbed by the superabsorbent polymer is not absorbed quickly, the residue will remain in contact with the skin for a long time, causing problems such as a poor wearing comfort and skin rashes, and therefore a faster absorption speed is required. Also, when used in actual sanitary products, the polymer chains in the superabsorbent polymer are destroyed by components such as ascorbic acid present in urine, and the mechanical properties of the resin, i.e., gel strength, decrease significantly as the wearing time increases, resulting in a decrease in various physical properties as well.

[0007] Therefore, research is needed to produce a superabsorbent resin that can achieve appropriate gel strength while maintaining the existing excellent absorption properties, taking into account the actual usage conditions of the product. Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention provides a superabsorbent resin that has improved absorption speed and gel strength while maintaining excellent absorption properties by using three types of additives in combination during polymerization, and a method for producing the same. [Means for solving the problem]

[0009] In order to solve the above problems, the present invention provides forming a hydrogel polymer comprising a crosslinked polymer obtained by crosslinking a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group in the presence of an epoxy-based internal crosslinking agent, a chelating agent and an encapsulated blowing agent; drying the hydrous gel polymer to form a base resin powder; and The method includes a step of heat-treating the base resin powder in the presence of a surface cross-linking agent to cross-link the surface of the base resin powder, The epoxy-based internal crosslinking agent has a weight average molecular weight of 200 kDa to 1,000 kDa; The capsule-type foaming agent has a structure including a core containing a hydrocarbon and a shell formed of a thermoplastic resin surrounding the core, and provides a method for producing a highly water-absorbent resin. Effect of the Invention

[0010] According to the method for producing a superabsorbent resin of the present invention, it is possible to provide a superabsorbent resin which exhibits excellent absorption performance, and at the same time has a high absorption rate and excellent gel strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention.

[0012] The singular term includes the plural term unless the context clearly indicates otherwise. In this specification, the terms "comprise", "comprise", "have" and the like are intended to specify the presence of embodied features, steps, components, or combinations thereof, and should be understood as not precluding the possibility of the presence or addition of one or more other features, steps, components, or combinations thereof.

[0013] The terms first, second, third, etc. are used to describe various elements, and such terms are used only to distinguish one element from another element.

[0014] Since the present invention can be modified in various ways and can have various forms, specific embodiments are exemplified and described in detail below. However, this is not intended to limit the present invention to the specific disclosed form, and it should be understood that the present invention includes all modifications, equivalents, and alternatives within the spirit and technical scope of the present invention.

[0015] The term "polymer" or "polymeric polymer" as used herein means a state in which a water-soluble ethylenically unsaturated monomer is polymerized, and may include any range of water content or particle size. Among the above polymers, a polymer having a water content (water content) of about 40% by weight or more in a state after polymerization and before drying may be referred to as a hydrogel polymer, and particles obtained by crushing and drying such a hydrogel polymer may be referred to as a crosslinked polymer.

[0016] In addition, the term "super absorbent resin powder" refers to a particulate material including a crosslinked polymer obtained by polymerizing a water-soluble ethylenically unsaturated monomer containing acidic groups and at least a portion of the acidic groups being neutralized, and crosslinking the polymer with an internal crosslinking agent.

[0017] In addition, the term "super absorbent polymer" refers to a crosslinked polymer obtained by polymerizing a water-soluble ethylenically unsaturated monomer containing an acidic group and at least a portion of the acidic group being neutralized, or a base resin in the form of a powder consisting of super absorbent polymer particles obtained by pulverizing the crosslinked polymer, depending on the context. Alternatively, the term "super absorbent polymer" is used to encompass all of the crosslinked polymers or base resins that have been subjected to additional processes, such as surface crosslinking, pulverization into fine powder, drying, pulverization, classification, etc., to be made into a state suitable for commercialization.

[0018] The term "internal crosslinking agent" used in this specification is a term used to distinguish it from the "surface crosslinking agent" for crosslinking the surface of the base resin, and serves to crosslink and polymerize the unsaturated bonds of the water-soluble ethylenically unsaturated monomer described above. The crosslinking in this step is performed without distinguishing between the surface and the inside, but the surface of the superabsorbent resin particles finally produced by the surface crosslinking process of the base resin described below has a structure crosslinked by the surface crosslinking agent, and the inside has a structure crosslinked by the internal crosslinking agent.

[0019] Hereinafter, the method for producing a superabsorbent polymer and the superabsorbent polymer will be described in more detail with reference to specific embodiments of the present invention.

[0020] A method for producing a superabsorbent resin according to one embodiment of the present invention includes the steps of: forming a hydrogel polymer comprising a crosslinked polymer obtained by crosslinking a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group in the presence of an epoxy-based internal crosslinking agent, a chelating agent, and a capsule-type blowing agent; drying the hydrogel polymer to form a base resin powder; and heat-treating the base resin powder in the presence of a surface crosslinking agent to crosslink a surface of the base resin powder.

[0021] When actually used as a sanitary material, superabsorbent polymers can remain in a swollen state for a long time due to urine, body fluids, etc., but in this case, the ascorbic acid component in urine and body fluids promotes the action of residual radicals inside the polymer, destroying the polymer chains, and as a result, the gel strength of the resin decreases significantly the longer it is worn in a swollen state, causing a problem that various water absorption properties also decrease due to changes in the internal structure.

[0022] The inventors therefore discovered that by using a combination of three types of additives at the polymerization stage of the superabsorbent resin, the synergistic effect of these additives can be achieved, resulting in excellent absorbent properties such as water retention and absorbency under pressure, a very fast initial absorption rate, and at the same time, excellent gel strength and improved surface feel, thereby arriving at the present invention.

[0023] Specifically, it was confirmed that the use of the specific capsule-type foaming agent of the present invention allows the superabsorbent resin to have a sufficiently large surface area and exhibit excellent initial absorption. As a result, such a superabsorbent resin can provide sanitary materials such as diapers and sanitary napkins that can quickly absorb body fluids and provide a dry feel. In addition, by using a specific epoxy-based crosslinking agent and a chelating agent in combination with this, a new crosslinking structure is formed by chemically bonding the polymer main chain with the structure formed by the capsule-type foaming agent and the chelating agent during the polymerization process, and this structure can achieve excellent absorption capacity and gel strength under pressure.

[0024] The superabsorbent polymer thus manufactured changes its gel contraction degree and water flow characteristics in response to external pressure while absorbing body fluids. Due to this structure, the superabsorbent polymer can exhibit improved absorption speed and gel strength.

[0025] Hereinafter, each step of the method for producing a superabsorbent polymer will be described in detail according to a specific embodiment of the present invention.

[0026] A method for producing a superabsorbent resin according to one embodiment of the present invention includes a step of forming a hydrogel polymer including a crosslinked polymer obtained by crosslinking a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group in the presence of an epoxy-based internal crosslinking agent, a chelating agent, and an encapsulated blowing agent.

[0027] The cross-linking polymerization step may be carried out by cross-linking a monomer composition containing, in addition to the above components, components that are generally used in the manufacture of superabsorbent resins.

[0028] First, the water-soluble ethylenically unsaturated monomer may be any monomer commonly used in the manufacture of superabsorbent resins. As a non-limiting example, the water-soluble ethylenically unsaturated monomer may be a compound represented by the following Chemical Formula 1:

[0029] [Chemical formula 1] R1-COOM 1

[0030] In the above Chemical Formula 1, R1 is an alkyl group having 2 to 5 carbon atoms and containing an unsaturated bond, M 1 is a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.

[0031] Preferably, the monomer may be at least one selected from the group consisting of acrylic acid, methacrylic acid, and monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts of these acids. In this way, when acrylic acid or a salt thereof is used as the water-soluble ethylenically unsaturated monomer, it is advantageous because a superabsorbent resin having improved water absorption can be obtained. In addition, the monomer may be at least one selected from the group consisting of anionic monomers of maleic anhydride, fumaric acid, crotonic acid, itaconic acid, 2-acryloylethanesulfonic acid, 2-methacryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, or 2-(meth)acrylamido-2-methylpropanesulfonic acid and their salts; nonionic hydrophilic monomers of (meth)acrylamide, N-substituted (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, or polyethylene glycol (meth)acrylate; and amino group-containing unsaturated monomers of (N,N)-dimethylaminoethyl (meth)acrylate or (N,N)-dimethylaminopropyl (meth)acrylamide and their quaternary derivatives.

[0032] Here, the water-soluble ethylenically unsaturated monomer has an acidic group, and at least a part of the acidic group is neutralized. Preferably, the monomer is partially neutralized with an alkaline substance such as sodium hydroxide, potassium hydroxide, or ammonium hydroxide.

[0033] At this time, the neutralization degree of the monomer may be 40 to 95 mol%, or 40 to 80 mol%, or 45 to 75 mol%. The range of the neutralization degree varies depending on the final properties, but if the neutralization degree is too high, the neutralized monomer precipitates and the polymerization is not smoothly carried out, and conversely, if the neutralization degree is too low, the water absorption of the polymer is greatly reduced and the polymer may exhibit properties similar to elastic rubber, which is difficult to handle.

[0034] In the superabsorbent resin of the embodiment, the hydrous gel polymer is a crosslinked polymer obtained by polymerizing the water-soluble ethylenically unsaturated monomer in the presence of an epoxy-based internal crosslinking agent, a chelating agent, and an encapsulated foaming agent.

[0035] The epoxy-based internal crosslinking agent is a component that introduces a new crosslinking structure into the polymer, and in particular contributes to improving gel strength by forming a uniform network. The epoxy-based internal crosslinking agent is an epoxy-based compound having a weight average molecular weight of 200 kDa to 1,000 kDa. Preferably, an epoxy-based compound having a weight average molecular weight of 300 kDa to 800 kDa or 500 kDa to 700 kDa is used.

[0036] When the weight average molecular weight of the epoxy-based internal crosslinking agent is less than 200 kDa, it is difficult to realize a high water retention capacity, and when it exceeds 1,000 kDa, there is a problem that the water retention capacity increases excessively.

[0037] Meanwhile, the weight average molecular weight was measured by gel permeation chromatography (GPC, PL GPC220, Agilent Technologies) under the following conditions.

[0038] - Column: PL Olexis (Polymer Laboratories) -Solvent: TCB (Trichlorobenzene) -Flow rate: 1.0ml / min -Sample concentration: 1.0mg / ml -Injection volume: 200μl -Column temperature: 160°C -Detector: Agilent High Temperature RI detector -Standard:Polystyrene (corrected by cubic function)

[0039] The epoxy-based internal crosslinking agent may have an epoxy equivalent of 100 g / eq to 400 g / eq, preferably 110 g / eq to 380 g / eq. If the epoxy equivalent of the epoxy-based crosslinking agent is less than 100 g / eq, the flexibility of the crosslinked polymer network may decrease, resulting in a problem of a decrease in the absorbency of the superabsorbent resin. Conversely, if the epoxy equivalent is high, such as 400 g / eq or more, it is difficult to form a uniform crosslinked structure.

[0040] Specific examples of the epoxy-based internal crosslinking agent include ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, poly(ethylene glycol) n diglycidyl ether (n = 4 to 13), and combinations thereof. Usable types of commercially available epoxy-based internal crosslinking agents include EJ-1030, EJ-831, EJ-841, etc., manufactured by JSI, but are not limited thereto.

[0041] The epoxy-based internal crosslinking agent can be used in an amount of 0.01 to 10 parts by weight, 0.03 to 5 parts by weight, or 0.05 to 3 parts by weight, based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. When used within the above content range, it is preferable because it can be used in combination with a chelating agent and a capsule-type blowing agent described below to maximize the synergistic effect.

[0042] The chelating agent is a component that contributes to improving the gel strength by binding with metal ions during the cross-linking polymerization stage of the polymer. 2+ The interaction with the metal ions prevents the polymer from being oxidized by the metal ions in the new crosslinked structure.

[0043] The chelating agent is one or more selected from the group consisting of ethylenediaminetetraacetic acid (EDTA), diethylenetriaminepentaacetic acid (DTPA), phenolic acid, citric acid, amino acids, and salts thereof. Preferably, ethylenediaminetetraacetic acid (EDTA), diethylenetriaminepentaacetic acid (DTPA) or sodium salts thereof can be used, and more preferably, tetravalent sodium salt of ethylenediaminetetraacetic acid (EDTA) or diethylenetriaminepentaacetic acid (DTPA) can be used.

[0044] The chelating agent can be used in an amount of 0.01 to 10 parts by weight, 0.03 to 5 parts by weight, or 0.1 to 3 parts by weight, based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. When used within the above content range, it is preferable because it can be used in combination with an epoxy-based internal crosslinking agent and a capsule-type foaming agent to maximize the synergistic effect.

[0045] The capsule type foaming agent is present in an encapsulated state during polymerization in the polymer and foams when heat is applied during the drying process described below, forming pores of appropriate size between the polymer structures of the superabsorbent resin, allowing the superabsorbent resin sheet to exhibit an open pore channel structure. In particular, the gel strength of the resin can be significantly improved by interacting with the (epoxy-based internal crosslinking agent).

[0046] The encapsulated foaming agent may have a structure including a core containing a hydrocarbon of a monomer composition and a shell formed of a thermoplastic resin surrounding the core. The expansion characteristics of such an encapsulated foaming agent vary depending on the components constituting the core and shell and the weight and diameter of each component, and by adjusting these, it is possible to expand to a desired size and adjust the porosity of the superabsorbent resin sheet.

[0047] Forming pores of appropriate size on the surface of resin particles can greatly improve the initial absorption capacity of the superabsorbent resin. Specifically, when the particle size of the resin particles is 300 μm to 425 μm, the appropriate pore size is about 20 μm to 200 μm. By using the above-mentioned capsule-type foaming agent, resin particles with pores of such size on the surface can be manufactured, but in order to mass-produce resin particles with pores of appropriate size, it is necessary to understand the expansion characteristics of the capsule-type foaming agent. However, the form in which the capsule-type foaming agent is foamed in the superabsorbent resin varies depending on the manufacturing conditions of the superabsorbent resin, so it is difficult to define it as one form. Therefore, by foaming the capsule-type foaming agent in air and checking the expansion ratio and size, it can be confirmed whether it is suitable for forming resin particles with pores of appropriate size.

[0048] Specifically, the encapsulated foaming agent is applied onto a glass Petri dish, and then heated in air at 150° C. for 10 minutes to expand the encapsulated foaming agent. When the encapsulated foaming agent shows a maximum expansion ratio in air of 3 to 15 times, 5 to 15 times, or 8.5 to 10 times, it can be determined that the encapsulated foaming agent is suitable for forming an appropriate open pore structure in the method for producing a superabsorbent resin sheet of the present invention.

[0049] The encapsulated foaming agent may have an average diameter of 5 μm to 50 μm, or 5 μm to 30 μm, or 5 μm to 20 μm, or 7 μm to 17 μm. When the encapsulated foaming agent has such an average diameter, it can be determined that it is suitable for achieving an appropriate porosity.

[0050] Furthermore, when the encapsulated foaming agent has a maximum expansion diameter in air of 20 μm to 190 μm, or 50 μm to 190 μm, or 70 μm to 190 μm, or 75 μm to 190 μm, it can be determined that the foaming agent is suitable for forming an appropriate open pore structure in the method for producing a superabsorbent resin sheet of the present invention.

[0051] The hydrocarbon constituting the core of the capsule type blowing agent may be one or more selected from the group consisting of n-propane, n-butane, iso-butane, cyclobutane, n-pentane, iso-pentane, cyclopentane, n-hexane, iso-hexane, cyclohexane, n-heptane, iso-heptane, cycloheptane, n-octane, iso-octane and cyclooctane. Among them, hydrocarbons having 3 to 5 carbon atoms (n-propane, n-butane, iso-butane, cyclobutane, n-pentane, iso-pentane, cyclopentane) are suitable for forming pores of the above-mentioned size, and iso-butane is the most suitable.

[0052] The thermoplastic resin constituting the shell of the capsule type foaming agent may be a polymer formed from one or more monomers selected from the group consisting of (meth)acrylate, (meth)acrylonitrile, aromatic vinyl, vinyl acetate, vinyl halide and vinylidene halide. Among them, a copolymer of (meth)acrylate and (meth)acrylonitrile is most suitable for forming pores of the above-mentioned size.

[0053] The encapsulated foaming agent may contain 10 to 30% by weight of hydrocarbon based on the total weight of the encapsulated foaming agent, which is most suitable for forming an open pore structure.

[0054] The encapsulated foaming agent may be manufactured or may be a commercially available foaming agent that satisfies the above-mentioned conditions. Examples of commercially available encapsulated foaming agents that can be used include F-36D from Matsumoto Honsha Co., Ltd. and MS-140DS from Dongjin Semichem Co., Ltd., but are not limited thereto.

[0055] In addition, the content of the encapsulated foaming agent can be 0.01 to 10 parts by weight, 0.03 to 5 parts by weight, or 0.1 to 3 parts by weight, based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. If the content of the encapsulated foaming agent is too low, an open pore structure is not properly formed, and if it is too high, the porosity is too high and the strength of the superabsorbent resin is weakened, so the above content ranges are preferable from this viewpoint.

[0056] Meanwhile, the crosslinked polymer may be crosslinked by further including a branched polymer of poly(meth)acrylic acid containing polyalkylene glycol in the side chain. That is, the branched polymer may be further included in the monomer composition. The branched polymer is poly(meth)acrylic acid containing polyalkylene glycol in the side chain, and can contribute to improving gel strength by acting as a physical crosslink inside the hydrogel polymer in the production of the superabsorbent resin.

[0057] Preferably, the branched polymer may be a copolymer in which polyethylene glycol and / or methoxypolyethylene glycol branches are bonded to a poly(meth)acrylic acid linear polymer.

[0058] More preferably, the branched polymer may be a copolymer containing a repeating unit represented by the following formula 1-1 and a repeating unit represented by the following formula 1-2.

[0059] [ka]

[0060] In the above Chemical Formula 1-1, Each R'1 is independently hydrogen or methyl;

[0061] [ka]

[0062] In the above Chemical Formula 1-2, Each R'2 is independently hydrogen or methyl; n is an integer from 1 to 100.

[0063] More preferably, the branched polymer may be a copolymer containing a repeating unit represented by the following formula 1-3.

[0064] [ka]

[0065] In the above Chemical Formula 1-3, Each R'3 is independently hydrogen or methyl; m is an integer from 1 to 100.

[0066] Preferably, the n and m each independently represent an integer of 1 to 50, more preferably an integer of 5 to 30, and most preferably an integer of 5 to 15.

[0067] Meanwhile, the branched polymer may have a weight average molecular weight of 10,000 to 100,000 g / mol, 20,000 to 50,000 g / mol, or 20,000 to 30,000 g / mol as measured by gel permeation chromatography (GPC, PL GPC220, Agilent Technologies) using PS standard.

[0068] Preferably, the branched polymer can be used in an amount of 0.01 to 10 parts by weight, or 0.01 to 5 parts by weight, based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. If the branched polymer is used in an amount of less than 0.01 parts by weight based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer, the content is too small to improve the gel strength, and if it is used in an amount of more than 10 parts by weight, the physical properties of the produced superabsorbent resin are reduced.

[0069] In the cross-linking polymerization step, a polymerization initiator generally used in the manufacture of superabsorbent resins may be included. As a non-limiting example, the polymerization initiator may be a thermal polymerization initiator or a photopolymerization initiator depending on the polymerization method, and in particular, a thermal polymerization initiator may be used. However, even in the photopolymerization method, a certain amount of heat is generated by irradiation with ultraviolet light, and a certain amount of heat is generated by the progress of the polymerization reaction, which is an exothermic reaction, so a thermal polymerization initiator may be additionally included.

[0070] The thermal polymerization initiator may be one or more compounds selected from the group consisting of persulfate initiators, azo initiators, hydrogen peroxide, and ascorbic acid.Specific examples of persulfate initiators include sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), and ammonium persulfate ((NH4)2S2O8). In addition, examples of azo initiators include 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, 2-(carbamoylazo)isobutylonitrile, 2,2-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 4,4-azobis-(4-cyanovaleric acid), and 4,4-azobis-(4-cyanovaleric acid). Examples of thermal polymerization initiators include aryl ethers such as aryl ethers, aryl ethers, and aryl ethers with aryl groups. More details on thermal polymerization initiators are disclosed in Odian's book "Principle of Polymerization" (Wiley, 1981), page 203, which can be referred to.

[0071] The photopolymerization initiator may be one or more compounds selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyl alkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine, and α-aminoketone. Specific examples of acylphosphine include diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and ethyl(2,4,6-trimethylbenzoyl)phenylphosphinate. More detailed information on photoinitiators is provided in Reinhold Schwalm's book "UV Coatings: Basics, Recent Developments and New Application" (Elsevier, 2007), p. 115, and is not limited to the above examples.

[0072] The polymerization initiator may be added at a concentration of about 0.0001 to 1 wt % or 0.001 to 1 wt % based on the monomer composition containing the water-soluble ethylenically unsaturated monomer. When a thermal polymerization initiator and a photopolymerization initiator are used simultaneously, the above content refers to the total mixed content.

[0073] That is, if the concentration of the polymerization initiator is too low, the polymerization rate is slowed down and a large amount of residual monomers may be extracted in the final product, which is undesirable, whereas if the concentration of the polymerization initiator is higher than the above range, the polymer chains forming the network are shortened, the content of water-soluble components is increased, and the physical properties of the resin, such as the compression absorption capacity, are degraded, which is undesirable.

[0074] In addition, the monomer composition may further contain additives such as a surfactant, a thickener, a plasticizer, a storage stabilizer, and an antioxidant, if necessary.

[0075] The surfactant induces uniform dispersion of the foaming agent and prevents the gel strength or density from decreasing due to uniform foaming during foaming. It is preferable to use an anionic surfactant as the surfactant. Specifically, the surfactant is SO3 - It contains an anion and a compound represented by the following chemical formula 2 can be used.

[0076] [Chemical formula 2] R-SO3Na

[0077] In the above Chemical Formula 2, R is an alkyl group having 8 to 16 carbon atoms.

[0078] In addition, the surfactant is preferably used in an amount of 300 ppmw or less based on the weight of the water-soluble ethylenically unsaturated monomer. If the amount of the surfactant used exceeds 300 ppmw, the content of the surfactant in the superabsorbent resin increases, which is not preferable. In addition, the surfactant is preferably used in an amount of 100 ppmw or more, or 150 ppmw or more based on the weight of the water-soluble ethylenically unsaturated monomer.

[0079] The monomer composition may be prepared in the form of a solution in which raw materials such as the monomer, polymerization initiator, and internal crosslinking agent are dissolved in a solvent.

[0080] In this case, the solvent that can be used is not limited in composition as long as it can dissolve the above-mentioned raw materials. For example, the solvent may be water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, N,N-dimethylacetamide, or a mixture thereof.

[0081] The formation of the hydrogel polymer by polymerization of the monomer composition may be carried out by a conventional polymerization method, and the process is not particularly limited. As a non-limiting example, the polymerization method is largely divided into thermal polymerization and photopolymerization depending on the type of polymerization energy source, and the thermal polymerization may be carried out in a reactor having a stirring shaft such as a kneader, and the photopolymerization may be carried out in a reactor equipped with a movable conveyor belt.

[0082] For example, the monomer composition is introduced into a reactor such as a kneader equipped with an agitator shaft, and hot air is supplied thereto or the reactor is heated to thermally polymerize the monomer composition to obtain a hydrogel polymer. Depending on the type of agitator shaft installed in the reactor, the hydrogel polymer is discharged from the outlet of the reactor in the form of particles of several millimeters to several centimeters. Specifically, the hydrogel polymer obtained is obtained in various forms depending on the concentration of the monomer composition injected and the injection speed, but the hydrogel polymer obtained usually has a weight average particle size of 2 to 50 mm.

[0083] As another example, when the monomer composition is photopolymerized in a reactor equipped with a movable conveyor belt, a sheet-like hydrogel polymer is obtained. In this case, the thickness of the sheet may vary depending on the concentration and injection speed of the monomer composition to be injected, but it is generally preferable to adjust the thickness to 0.5 to 5 cm in order to ensure the production speed while ensuring that the entire sheet is evenly polymerized.

[0084] The water content of the hydrogel polymer obtained by the above method is usually 40 to 80 wt%. Meanwhile, the "water content" is the amount of water contained in the total weight of the hydrogel polymer, and means the weight of the hydrogel polymer minus the weight of the polymer in a dry state. Specifically, it is defined as a value calculated by measuring the weight loss due to evaporation of water in the polymer during the process of drying by increasing the temperature of the polymer using infrared heating. At this time, the drying conditions are room temperature, about 180°C, and maintained for about 40 minutes to measure the water content.

[0085] Next, the method for producing the superabsorbent polymer according to an embodiment of the present invention includes a step of drying the produced hydrogel polymer to form a base resin powder. The drying step causes the capsule-type foaming agent to foam and form pores of appropriate size between the polymer structures of the superabsorbent polymer, so that the superabsorbent polymer sheet exhibits an open pore channel structure, thereby improving the absorption speed of the superabsorbent polymer produced.

[0086] Meanwhile, if necessary, a coarse pulverization step may be performed before drying in order to increase the efficiency of the drying step.

[0087] In this case, the pulverizer used is not limited in configuration, and specifically may include any one selected from the group of pulverizing devices consisting of a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a chopper, and a disc cutter, but is not limited to the above examples.

[0088] In this case, the polymer may be pulverized to a particle size of about 2 to about 10 mm in the pulverization step.

[0089] It is technically difficult to crush the hydrogel polymer to a particle size of less than 2 mm due to its high water content, and the crushed particles may aggregate with each other. On the other hand, crushing the hydrogel polymer to a particle size of more than 10 mm has little effect on increasing the efficiency of the subsequent drying step.

[0090] Drying is carried out on the polymer either as-polymerized, which may be ground as described above, or which has not been subjected to a grinding step.

[0091] The drying temperature in the drying step may be about 150°C to 250°C. If the drying temperature is less than 150°C, the foaming agent is not sufficiently foamed, and the drying time is excessively long, which may deteriorate the physical properties of the superabsorbent resin finally formed. If the drying temperature is more than 250°C, only the polymer surface is dried excessively, which may cause fine powder to be generated in the subsequent pulverization process, which may deteriorate the physical properties of the superabsorbent resin finally formed. Therefore, the drying may be preferably performed at a temperature of about 150°C to 230°C, more preferably about 180°C to 200°C. Meanwhile, the drying time is performed for about 10 minutes to 120 minutes, preferably about 20 minutes to 90 minutes, taking into consideration the process efficiency, but is not limited thereto.

[0092] The drying method of the drying step can be selected and used without any limitation on the configuration as long as it is a method commonly used for drying hydrogel polymers. Specifically, the drying step can be performed by a method such as hot air supply, infrared radiation, ultrashort wave radiation, or ultraviolet radiation. The water content of the polymer after the drying step can be about 5 to about 10% by weight.

[0093] According to one embodiment of the present invention, the dried polymer obtained through the drying step may be further pulverized.

[0094] The particle size of the base resin, which is a polymer powder obtained after the pulverization step, may be about 150 μm to 850 μm. The pulverizer used to pulverize to such a particle size may be, for example, a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, or a jog mill, but the present invention is not limited to the above examples.

[0095] In order to control the physical properties of the superabsorbent resin powder that is the final product after the pulverization step, the base resin obtained after pulverization is classified according to particle size. Preferably, polymers having a particle size of about 150 μm to 850 μm are classified, and only the base resin having such a particle size can undergo the surface crosslinking reaction step.

[0096] Meanwhile, according to one embodiment of the present invention, after forming the base resin powder, the method includes a step of heat-treating the base resin powder in the presence of a surface cross-linking agent to cross-link the surface of the base resin powder.

[0097] The surface crosslinking step is a step of forming a surface crosslinked layer using a surface crosslinking agent to increase the surface crosslinking density of the base resin, and the unsaturated bonds of the water-soluble ethylenically unsaturated monomer that remained on the surface without being crosslinked are crosslinked by the surface crosslinking agent, thereby forming superabsorbent resin particles with a high surface crosslinking density. The surface crosslinking density, i.e., the external crosslinking density, increases by this heat treatment process, while the internal crosslinking density remains unchanged, and the superabsorbent resin with the surface crosslinked layer thus produced has a structure in which the external crosslinking density is higher than the internal crosslinking density.

[0098] In one embodiment of the method, a surface cross-linking agent composition containing a surface cross-linking agent, an alcohol-based solvent, and water can be used in the step of forming the surface cross-linked layer.

[0099] Meanwhile, the surface cross-linking agent contained in the surface cross-linking agent composition can be any surface cross-linking agent that has been used in the manufacture of superabsorbent resins in the past, without any particular limitations. For example, the surface cross-linking agent can include one or more polyols selected from the group consisting of ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,2-hexanediol, 1,3-hexanediol, 2-methyl-1,3-propanediol, 2,5-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, tripropylene glycol and glycerol; one or more carbonate-based compounds selected from the group consisting of ethylene carbonate and propylene carbonate; epoxy compounds such as ethylene glycol diglycidyl ether; oxazoline compounds such as oxazolidinone; polyamine compounds; oxazoline compounds; mono-, di- or polyoxazolidinone compounds; or cyclic urea compounds; and the like. Preferably, the same internal crosslinking agent as described above can be used, for example, a diglycidyl ether compound of alkylene glycol such as ethylene glycol diglycidyl ether can be used.

[0100] Such a surface cross-linking agent can be used in an amount of 0.001 to 2 parts by weight relative to 100 parts by weight of the base resin. For example, the surface cross-linking agent can be used in an amount of 0.005 parts by weight or more, 0.01 parts by weight or more, or 0.02 parts by weight or more, and 0.5 parts by weight or less, or 0.3 parts by weight or less, relative to 100 parts by weight of the base resin. By adjusting the content range of the surface cross-linking agent within the above range, a superabsorbent resin exhibiting various physical properties such as excellent absorption performance and liquid permeability can be produced.

[0101] Meanwhile, the surface cross-linked layer may further include an additive. For example, aluminum sulfate and / or silica may be further included as an additive to suppress caking. It is expected that the aluminum sulfate uniformly included in the surface cross-linked layer can improve the overall strength of the superabsorbent resin particles and improve the liquid permeability since the particle shape is maintained even after absorbing liquid.

[0102] Meanwhile, the superabsorbent resin according to one embodiment of the invention may have a particle size of 150 to 850 μm. More specifically, at least 95% by weight of the base resin powder and the superabsorbent resin containing the base resin powder have a particle size of 150 to 850 μm, and may contain 50% by weight or more of particles having a particle size of 300 to 600 μm, with less than 3% by weight of fine powder having a particle size of less than 150 μm.

[0103] In addition, the superabsorbent resin according to one embodiment of the present invention can provide a superabsorbent resin that maintains excellent absorption performance such as basic water retention ability while simultaneously improving the absorption speed and excellent gel strength.

[0104] Specifically, 2.5 g of the superabsorbent polymer is immersed in 50 g of ascorbate water and swollen in a 40° C. oven for 24 hours, and the gel strength of the swollen superabsorbent polymer measured using a tensile compression tester is 0.50 N or more. Preferably, the gel strength is 0.50 N to 0.9 N, more preferably, 0.6 N to 0.85 N or 0.65 N to 0.8 N. The ascorbate water refers to an aqueous solution of 0.9 wt % sodium chloride (NaCl) and 0.005 wt % ascorbic acid.

[0105] The gel strength is an index showing resistance to degradation by L-ascorbic acid contained in urine, body fluids, etc., and the method for measuring the gel strength will be described in more detail in the Experimental Examples section below.

[0106] The superabsorbent polymer has an absorption speed of 50 seconds or less as measured by a Vortex method. Preferably, the absorption speed is 48 seconds or less, about 46 seconds or less, or 43 seconds or less. The smaller the value, the better the absorption speed is, and the lower limit of the absorption speed is theoretically 0 seconds, but for example, the absorption speed may be about 10 seconds or more, about 15 seconds or more, or about 20 seconds or more.

[0107] The absorption rate was measured in seconds according to the method described in WO 1987 / 003208. Specifically, the absorption rate (or vortex time) was calculated by adding 2 g of the superabsorbent polymer to 50 mL of physiological saline at 23°C to 24±1°C, stirring with a magnetic bar (diameter 8 mm, length 31.8 mm) at 600 rpm, and measuring the time in seconds until the vortex disappeared. It can be said that the shorter the time, the faster the initial absorption rate of the superabsorbent polymer.

[0108] The centrifugation water retention capacity (CRC) measured according to EDENA method WSP241.2 is 36.5 g / g or more, preferably 36.5 g / g to 45.0 g / g, or 36.5 g / g to 40.0 g / g. The method for measuring the centrifugation water retention capacity will be described in more detail in the experimental examples section below.

[0109] The absorbent capacity under pressure (AUP) at 0.7 psi measured according to EDANA method WSP242.3-10 is 17 g / g or more, preferably 17.0 g / g to 21.0 g / g, 17.5 g / g or more, or 18.0 g / g or more. The method for measuring the absorbent capacity under pressure (AUP) will be described in more detail in the experimental examples section below.

[0110] The superabsorbent resin obtained by the above-mentioned preparation method can provide a superabsorbent resin which has improved properties such as a faster absorption rate and excellent gel strength while maintaining excellent absorption performance such as basic water retention capacity.

[0111] The functions and effects of the present invention will be described in more detail below with reference to specific examples of the present invention, however, these examples are merely presented as examples of the present invention and do not define the scope of the invention.

[0112] [Example] <Production of superabsorbent resin> Example 1 In a 3L glass container equipped with an agitator, nitrogen injector, and thermometer, 100g of acrylic acid, 123.5g of 32% caustic soda (NaOH), 0.2g of sodium persulfate as a thermal polymerization initiator, 0.008g of diphenyl (2,4,6-trimethylbenzoyl)-phosphine oxide as a photopolymerization initiator, 0.06g of ethylene glycol diglycidyl ether, 0.1g of capsule type foaming agent (F-36D, SDI Korea), 0.09g of 28% sodium dodecyl sulfate aqueous solution, 59g of water, 0.3g of a branched polymer containing a repeating unit of the following formula 3'-1, and 0.1g of EDTA-4Na were mixed to prepare a monomer composition with a total solid concentration of 43% by weight. The monomer composition was supplied at a supply rate of 500 mL / min to 2,000 mL / min onto a rotating belt having a width of 10 cm and a length of 2 m, rotating at a speed of 50 cm / min. 2 The mixture was irradiated with ultraviolet light having an intensity of 1000 nm for 60 seconds to carry out a polymerization reaction.

[0113] [ka]

[0114] After the polymerization reaction had progressed, the product was cut with a meat chopper and dried in an air-flow oven at 185° C. for 40 minutes.

[0115] 100g of the prepared base resin powder was mixed for 2 minutes with a mixture of 4g ultrapure water, 0.5g propylene glycol, 0.10g epoxy surface crosslinking agent (EJ-1030, JSI Co.), 0.2g aluminum sulfate, and 0.06g Aerosil 200. This was dried at 140°C for 40 minutes and then classified to obtain particles with a size of 150~850μm to prepare a superabsorbent resin.

[0116] Examples 2 to 9 A superabsorbent polymer composition was prepared in the same manner as in Example 1, except that the components and amounts shown in Table 1 below were used in the polymerization step.

[0117] Comparative Example 1 In a 3L glass container equipped with a stirrer, nitrogen injector, and thermometer, 100g of acrylic acid, 123.5g of 32% caustic soda (NaOH), 0.2g of sodium persulfate as a thermal polymerization initiator, 0.008g of diphenyl (2,4,6-trimethylbenzoyl)-phosphine oxide as a photopolymerization initiator, 0.2g of diacrylate, 0.1g of capsule type foaming agent (F-36D, SDI Korea), 0.09g of 28% sodium dodecyl sulfate aqueous solution, and 59g of water were mixed to prepare a monomer composition with a total solid concentration of 43% by weight. The monomer composition was supplied at a supply rate of 500mL / min to 2,000mL / min on a rotating belt having a width of 10cm and a length of 2m, rotating at a speed of 50cm / min. At the same time as the supply of the monomer composition, a 10mW / cm2 The mixture was irradiated with ultraviolet light having an intensity of 1000 nm for 60 seconds to carry out a polymerization reaction.

[0118] After the polymerization reaction had progressed, the product was cut with a meat chopper and dried in an air-flow oven at 185° C. for 40 minutes.

[0119] 100g of the prepared base resin powder was mixed for 2 minutes with a mixture of 7g ultrapure water, 0.5g propylene glycol, 0.10g epoxy surface crosslinking agent (EJ-1030, JSI Co.), 0.8g aluminum sulfate, and 0.04g Aerosil 200. This was dried at 140°C for 40 minutes and then classified to obtain particles with a size of 150~850μm to prepare a superabsorbent resin.

[0120] Comparative Examples 2 to 3 A superabsorbent resin composition was prepared in the same manner as in Comparative Example 1, except that the components and amounts shown in Table 1 below were used as the components in the polymerization step.

[0121] Comparative Examples 4 and 5 A superabsorbent polymer composition was prepared in the same manner as in Example 1, except that the components and amounts shown in Table 1 below were used in the polymerization step.

[0122] [Table 1]

[0123] <Experimental Example> The properties of the superabsorbent resin compositions produced in the above Examples and Comparative Examples were evaluated by the following methods. The results are shown in Table 2.

[0124] Unless otherwise specified, all of the following physical property evaluations were performed at room temperature (25°C), and saline or salt water refers to a 0.9 wt% sodium chloride (NaCl) aqueous solution. The ascorbate solution refers to a 0.9 wt% sodium chloride (NaCl) and 0.005 wt% ascorbic acid aqueous solution.

[0125] (1)Centrifuge Retention Capacity (CRC) The superabsorbent resin particles having a particle size of 150 μm to 850 μm were taken and the centrifuge retention capacity (CRC) was measured based on the no-load absorbency in accordance with the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP241.2.

[0126] Specifically, resins obtained from the examples and comparative examples were classified using a sieve of #30-50 to obtain resins. Such resins W0(g) (approximately 0.2g) were evenly placed in a nonwoven fabric envelope, sealed, and then immersed in physiological saline (0.9% by weight) at room temperature. After 30 minutes, the envelope was dried for 3 minutes under conditions of 250G using a centrifuge, and the mass W2(g) of the envelope was measured. The same operation was also performed without using resin, and the mass W1(g) at that time was measured. Using each of the obtained masses, CRC(g / g) was calculated using the following formula.

[0127] [Formula 1] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1

[0128] (2) Absorbency Under Pressure (AUP) The 0.7 psi pressure absorbency of each resin was measured according to EDANA method WSP242.3-10. The resin fractions used in the CRC measurement were used for the pressure absorbency measurement.

[0129] Specifically, a stainless steel 400 mesh wire net was attached to the bottom of a plastic cylinder with an inner diameter of 25 mm. Under conditions of room temperature and humidity of 50%, water-absorbent resin W0(g) (0.16 g) was evenly spread on the wire net, and a piston capable of applying a load of 0.7 psi evenly on top of it was made slightly smaller in outer diameter than 25 mm, with no gap between it and the inner wall of the cylinder and allowing unhindered up and down movement. At this time, the weight W3(g) of the device was measured.

[0130] A glass filter with a diameter of 90 mm and a thickness of 5 mm was placed inside a Petri dish with a diameter of 150 mm, and physiological saline composed of 0.9 wt% sodium chloride was placed at the same level as the upper surface of the glass filter. A sheet of filter paper with a diameter of 90 mm was placed on top of the glass filter. The measuring device was placed on the filter paper, and the liquid was absorbed under a load for one hour. After one hour, the measuring device was lifted and its weight W4 (g) was measured.

[0131] The obtained masses were used to calculate the absorbency under pressure (g / g) according to the following formula.

[0132] [Formula 2] AUP(g / g)=[W4(g)-W3(g)] / W0(g)

[0133] (3) Absorption speed (Vortex,sec) Among the superabsorbent polymers, those with particle sizes of 150 to 850 μm were selected, and 2 g of the superabsorbent polymer was placed in 50 mL of physiological saline at 24 ± 1°C. The polymer was stirred at 600 rpm with a magnetic bar (diameter 8 mm, length 31.8 mm), and the time until the vortex disappeared was measured in seconds and calculated.

[0134] (4) Gel Strength (N) Among the superabsorbent polymers, those having a particle size of 150 μm to 850 μm were taken, and 2.5 g of the superabsorbent polymer was immersed in 50 g of ascorbate water and allowed to swell in an oven at 40° C. for 24 hours, and the gel strength of the swollen superabsorbent polymer was measured using a tensile compression tester.

[0135] Specifically, the swollen superabsorbent resin is measured using a digital force gauge FGP-2, which is a tension and compression tester, and the peak value of the force (N) applied to the tip due to penetration is measured three times under the following conditions, and the arithmetic average value is taken as the gel strength (unit: N).

[0136] Tip size: terminal diameter 10±0.1 mm Beaker size: 50±0.1 mm Penetration speed:500±0.5 mm / min

[0137] The physical properties of the highly water-absorbent resins after surface cross-linking for the above-mentioned Examples and Comparative Examples are shown in Table 2 below.

[0138] [Table 2]

[0139] Referring to the data in Table 2, it was confirmed that the superabsorbent resin of the embodiment produced according to the present invention has excellent absorption properties such as water retention capacity and absorbency under pressure, and has a very fast initial absorption speed while also achieving excellent gel strength by using three specific additives in combination during the polymerization stage.

[0140] In contrast, in the case of the examples that do not contain some of the three additives of the present invention, it was difficult to form the desired crosslinked structure, and therefore it was difficult to simultaneously achieve excellent absorption performance and gel strength. In particular, it was confirmed that the gel strength was significantly reduced compared to the examples.

Claims

1. A step of forming a hydrogel polymer comprising a crosslinked polymer obtained by crosslinking a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group in the presence of an epoxy-based internal crosslinking agent, a chelating agent and an encapsulated blowing agent; drying the hydrous gel polymer to form a base resin powder; and The method includes a step of heat-treating the base resin powder in the presence of a surface cross-linking agent to cross-link the surface of the base resin powder, The epoxy-based internal crosslinking agent has a weight average molecular weight of 200 kDa to 1,000 kDa; The capsule-type foaming agent has a structure including a core containing a hydrocarbon and a shell formed of a thermoplastic resin surrounding the core.

2. Relative to 100 parts by weight of the water-soluble ethylenically unsaturated monomer, 2. The method for producing a highly water-absorbent resin according to claim 1, comprising: 0.01 to 10 parts by weight of an epoxy-based internal crosslinking agent; 0.01 to 10 parts by weight of a chelating agent; and 0.01 to 10 parts by weight of a capsule-type blowing agent.

3. 3. The method for producing a highly water-absorbent resin according to claim 1, wherein the epoxy-based internal crosslinking agent has an epoxy equivalent of 100 g / eq to 400 g / eq.

4. The method for producing a superabsorbent resin according to any one of claims 1 to 3, wherein the chelating agent is at least one selected from the group consisting of ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, phenolic acid, citric acid, amino acids, and salts thereof.

5. The capsule type foaming agent is The hydrocarbon is at least one selected from the group consisting of n-propane, n-butane, iso-butane, cyclobutane, n-pentane, iso-pentane, cyclopentane, n-hexane, iso-hexane, cyclohexane, n-heptane, iso-heptane, cycloheptane, n-octane, iso-octane, and cyclooctane; The method for producing a superabsorbent resin according to any one of claims 1 to 4, wherein the thermoplastic resin is a polymer formed from one or more monomers selected from the group consisting of (meth)acrylate, (meth)acrylonitrile, aromatic vinyl, vinyl acetate, vinyl halide, and vinylidene halide.

6. The method for producing a highly water-absorbent resin according to claim 1 , wherein the crosslinked polymer is crosslinked and polymerized further containing a branched polymer of poly(meth)acrylic acid containing polyalkylene glycol in a side chain.

7. The highly water-absorbent resin according to claim 6, wherein the branched polymer is contained in an amount of 0.01 to 10 parts by weight based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer.

8. The method for producing a superabsorbent polymer according to any one of claims 1 to 7, wherein the drying step is carried out at a temperature of 150°C to 250°C for 10 minutes to 120 minutes.

9. 9. The method for producing a superabsorbent polymer according to claim 1, wherein the superabsorbent polymer has a gel strength of 0.50 N or more as measured by a tensile / compression tester after immersing 2.5 g of the superabsorbent polymer in 50 g of ascorbate water and swelling the polymer in an oven at 40° C. for 24 hours.

10. The method for producing a superabsorbent polymer according to claim 1 , wherein the superabsorbent polymer has an absorption speed of 50 seconds or less when measured by a vortex method.

11. The method for producing a superabsorbent polymer according to any one of claims 1 to 10, wherein the superabsorbent polymer has a centrifugation retention capacity (CRC) of 36.5 g / g or more as measured according to EDENA method WSP241.

2.

12. The method for producing a superabsorbent polymer according to any one of claims 1 to 11, wherein the superabsorbent polymer has an absorbency under pressure (AUP) of 17 g / g or more at 0.7 psi as measured according to EDANA method WSP242.3-10.